Manufacturer’s R&D Investment Strategy and Pricing Decisions in a Decentralized Supply Chain - Hengyun Zhang; Dingjun Hong (Discrete Dynamics in Nature and Society)
Consider that a manufacturer Stackelberg supply chain consists of an upstream supplier and a downstream manufacturer. The manufacturer purchases a component from the supplier and then transforms it into a final product which is sold in a price and quality sensitive market. The manufacturer considers to make R&D investment to improve the product quality and reduce the production cost. We first investigate and derive the optimal investment strategy and pricing decisions by establishing a three-stage game model. We show that the optimal investment strategy and pricing decisions in the decentralized model may deviate from those in the centralized model. We then propose a mechanism to coordinate the decentralized supply chain, by introducing a profit sharing policy, a production cost sharing policy, and an investment cost sharing policy. Finally, we show that both the supplier and the manufacturer can benefit from participating in the proposed coordination mechanism.